Od Biblioteki Towarzystwa Tatrzańskiego do Centralnej Biblioteki Górskiej PTTK w Krakowie – 135 lat historii - Górska, Agnieszka (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The article describes history and the tradition of the Central Mountain Library of Polish Tourist Country-Lovers’ Society in Cracow during the 135 year period of activity. It presents a formation of the library, her transformations, sets and distinguished librarians. The origins of the Central Mountain Library can be traced to the founding of the Tatra Society in 1874. There are many outstanding work concerning tourisms, geography, geology, ethnography, archaeology, architecture and mountain issues from 18th century, and ending on 21st century. The Central Mountain Library has great collection of works specialized on such subjects as ecology, geology, hill-walking and the place of mountains in art and literature are also purchased. It has became an important centre for the study of mountains, mountaineering and associated topics. This library constitutes unusually valuable and endless source up till today to the research on history and the development of Podhale, Tatras and other mountain ranges.